Advanced FVTD Simulation of Dielectric Resonator Antennas and Feed Structures - Fumeaux, Christophe; Baumann, Dirk; Vahldieck, Rüdiger (Applied Computational Electromagnetics Society Journal (ACES), 2022)
This paper illustrates the application of the Finite- Volume Time-Domain (FVTD) method to the electromagnetic modeling of complex 3D antenna structures. The FVTD algorithm solves Maxwell's equations in a conformal polyhedral mesh, therefore permitting an accurate approximation of curved surfaces and a fine resolution of structural details. The flexibility of the unstructured mesh is coupled with a geometry-matched local time-stepping scheme to increase the computational efficiency. The FVTD algorithm is applied here to simulate probe-fed hemispherical dielectric resonator antennas. Emphasis of the investigation is placed on the modeling of fabrication details and their influence on the input impedance and resonance frequency of the device.